Tour Guide Backpacker Application Designing Bengkulu City Based on Android - Haris Munandar; Agung Kharisma Hidayah (Penerbit ADM, 2021)
One of the trends in enjoying tourism that is currently developing is backpacking. Generally, backpackers are young tourists who want new experiences by doing tours at the least possible cost, they use conventional tourist transportation models and carry out their activities freely without hiring the services of a tour company. Backpacking has its own advantages but there are some issues especially for beginner backpackers. They will experience difficulties when traveling to an area that is rarely visited by other backpackers. For that we need an application that can be used as a reference for beginner backpackers who want to visit tourist areas, especially the city of Bengkulu. Applications that can accommodate data needs of a backpacker, especially regarding cheap hotel data, types of city transportation to take, recommended tourist attractions including the amount of costs required. The application will be integrated with firebase control so that the application becomes dynamic because the data is obtained from the database. To complete the application, the author will also use the google map API for more details about tourist locations, restaurants and inns that the user wants to visit. The frond end application can be run on the android operating system and is built using the java and xml programming languages, while the back end application is built using PHP and MySQL. To be able to display the map requires a separate API which is obtained from the google console. Applications use JSON data as a link between the front end and back end of the application. It is hoped that this application can help novice backpackers enjoy their travels in Bengkulu City which at the same time can be a guide for beginner backpackers who have never backpacked and do not understand the right and safe ways to travel to certain destinations with minimal costs.